Clinical, etiological profile and outcomes of convulsive refractory and non-refractory status epilepticus at a tertiary care centre: A prospective observational study - Nishant Gopaal; Dhan Raj Bagri; Jagdish Narayan Sharma (Wolters Kluwer Medknow Publications, 2022)
Introduction: Epidemiological data on childhood status epilepticus (SE) limited in India. This study depicts clinical profiles, etiology, and outcomes of convulsive refractory SE (RSE) and compares the results with cases of nonrefractory SE (NRSE). Subjects and Methods: This observational, cross-sectional study enrolled 300 children aged 1 month to 18 years, presenting with convulsive SE at a tertiary care hospital. Details of children who progressed to RSE were compared to those without RSE. Results: In the acute symptomatic etiology group, common causes for RSE were central nervous system infections (33.8%), cryptogenic etiology (13.8%), and remote symptomatic etiology (7%). RSE iwas associated with a higher rate of complications (58% Vs 24%) as compared to NRSE. Thirty percent of cases that progressed to RSE needed ventilator support as compared to only 8% of cases in the NRSE group. RSE was also associated with higher rates of shock (25%), AKI (16%), transaminitis (25%), acute liver failure (5.69%), multiple organ dysfunction score (12.6%), and acidosis (53%) as compared to NRSE. RSE was associated with higher mortality (28%) and morbidity (32%) as compared to NRSE cases. Cryptogenic etiology led to the highest mortality (33.3%) in cases of RSE while acute symptomology was associated with the highest morbidity (62%). Conclusions: RSE is a serious pediatric emergency that requires prompt recognition and management. Clinical knowledge and early administration of appropriate antiepileptic drugs at health-care facilities is the key to reduce morbidity and mortality.